Prosocial Behavior dan Persepsi Akuntabilitas Pengelolaan Dana Desa Dalam Konteks Budaya Tri Hita Karana - Mahayani, Ni Luh Ayu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 12 No 2 (2017), 2017)
ABSTRACT This study aims to examine the influence of competence, participation, and leadership with prosocial behavior as a moderating variable in accountability of village fund management.The analysis unit of this study are the village officials in Karangasem Regency in the year 2016. Data were collected through questionnaires and the samples are chosen by cluster random sampling. Data analysis technique used in this study is the analysis of partial least squares (PLS). The test results showed that the competence a positive effect on the village fund management accountability. P articipation of  the community gave a positive effect on the village fund management accountability. Prosocial behavior weakens the influence of the human resources competence on the village fund management accountability. Prosocial behavior strengthen the influence of community participation in village fund management accountability. Prosocial behavior weakens the influence of leadership on the village funds management accountability. Keywords : Village funds accountability, culture Tri Hita Karana, prosocial behavior